1977
DOI: 10.1093/infdis/135.supplement.s69
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Due to Bacteroidaceae: A Review of 92 Cases

Abstract: The clinical courses of 92 patients who had bacteremia due to Bacteroidaceae were reviewed. The overall mortality rate was 21% (19 patients). There was no significant difference between mortality rates when patients were grouped by anticipated clinical course of underlying disease (nonfatal, ultimately fatal, and rapidly fatal) and when they were grouped by type of antibacterial therapy (appropriate, including clindamycin, chloramphenicol, lincomycin, and carbenicillin; or inappropriate, signifying no antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1979
1979
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Members of the B. fragilis group are the commonest of the intestinal anaerobes isolated from bacteremia (4,15). It is generally accepted that this group of organisms is also the most frequently isolated from other anaerobic infections (12,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the B. fragilis group are the commonest of the intestinal anaerobes isolated from bacteremia (4,15). It is generally accepted that this group of organisms is also the most frequently isolated from other anaerobic infections (12,18).…”
Section: Discussionmentioning
confidence: 99%
“…The pH was adjusted to 7.3 with 1 N NaOH. Amounts (6 ml) were dispensed in screw-capped tubes and autoclaved at 12 lb for 15 Procedure. The NCCLS agar dilution proposed reference method was used to determine the minimum inhibitory concentration of eight antimicrobial agents.…”
mentioning
confidence: 99%
“…In general, there are numerous studies to show that agents with good in vitro activities against a broad range of anaerobic pathogens are more likely to produce favorable clinical outcomes than less active agents (2,10,11,13,15,16). Several studies showed lower mortality rates in patients with anaerobic bacteremia treated with appropriate antimicrobial agents than in patients receiving poorly active drugs (4,5,17,20). More difficult, however, may be the attempt to correlate specific susceptibility results with clinical success or failure in individual cases.…”
Section: Clinical Correlation Withmentioning
confidence: 99%
“…B. fragilis is usually recovered from intraabdominal infections (2,19,22), whereas B. bivius is frequently isolated from obstetric and gynecologic infections (1,12,33). Both species produce a ,-lactamase which may play an important role in their resistance to P-lactams (15,16,25,32,37).…”
mentioning
confidence: 99%